IMPLEMENTASI NILAI PANCASILA MELALUI BUDAYA SEKOLAH SEBAGAI IDENTITAS MANUSIA INDONESIA DI SEKOLAH DASAR - Ratu, Ratu Amalia Sari; Putri Sriwahyuni; Pooja Rekha Larasati; Rani Puspita Ayu; Rama Dhani (Study program PGSD FKIP Universitas Bung Hatta, 2024)
This research aims to understand the application of Pancasila as Indonesia's national identity through school rituals. This research uses a qualitative descriptive research design combined with ethnographic research. Data sources for this research include school principals, teachers and students. Furthermore, secondary data from this research comes from school documents relating to school days. Data collection techniques used in this research include observation and interviews. This research focuses on research concepts related to data analysis, including data reduction, data processing, and data interpretation. The results of this research are a revision of Pancasila which is very important in the formation of Indonesian identity and must be carried out from the start. All students at Al-Falah Islamic Elementary School have appreciation and appreciation for the values of Pancasila and diversity, so that these values can continue to be applied in everyday life as the identity of the Indonesian nation.